CORRELATION BETWEEN PLATELET COUNT AND BOTH LIVER FIBROSIS AND SPLEEN DIAMETER IN PATIENTS WITH SCHISTOSOMIASIS MANSONI - MEDEIROS,Tibério B (2014)
Context Studies have described the correlation between platelet count and the stages of fibrosis in chronic viral hepatitis, but few publications have studied this correlation in Schistosomiasis mansoni. Objectives Therefore, this study aimed to correlate platelet count with both the periportal fibrosis pattern and spleen diameter evaluated by ultrasound exam in patients with Schistosomiasis mansoni. Methods Patients with Schistosomiasis mansoni were evaluated by abdominal ultrasound by a single examiner for the determination of periportal fibrosis pattern (Niamey classification) and spleen diameter. Platelet counts were performed in an automated cell counter. Results One hundred eighty-seven patients with Schistosomiasis mansoni (mean age: 50.2 years) were included in the study, 114 of whom (61%) were women. Based on the Niamey classification, the ultrasound analysis revealed that 37, 64, 64 and 22 patients exhibited patterns C, D, E and F, respectively. In these four groups, the mean number of platelets was 264, 196, 127 and 103 x 109/L and mean spleen diameter was 9.2, 11.9, 14.9 and 16.2 centimeters, respectively. A reduction in platelet count was significantly associated with both the progression of the periportal fibrosis and the increase in spleen size. Conclusions Platelet count in patients with Schistosomiasis mansoni was inversely correlated with the severity of periportal fibrosis and spleen diameter.